Exact, approximate solutions and error bounds for coupled implicit systems of partial differential equations - Lucas Jódar (International Journal of Mathematics and Mathematical Sciences)
In this paper coupled implicit initial-boundary value systems of second order partial differential equations are considered. Given a finite domain and an admissible error ϵ an analytic approximate solution whose error is upper bounded by ϵ in the given domain is constructed in terms of the data.